Forest edge effects on medicinal plants diversity in lowland forest in Gunung Tilu, West Java, Indonesia - NINA HERLINA; IMAM WIDHIONO; ELLY PROKLAMASININGSIH; EMING SUDIANA; IING NASIHIN; NURDIN NURDIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Herlina N, Widhiono I, Proklamaningsih E, Sudiana E, Nasihin I, Nurdin. 2025. Forest edge effects on medicinal plants diversity in lowland forest in Gunung Tilu, West Java, Indonesia. Biodiversitas 26: 2873-2881. Forest edge effect is an ecological phenomenon that affects diversity of medicinal plants in the border area between forest edge and the interior. Gunung Tilu in West Java, Indonesia, is a lowland forest area with abundant natural resource potential, but the surrounding communities often use various resources in the form of wood and non-wood forest products, specifically medicinal plants which might cause edge effect. This study aims to analyze the diversity of medicinal plants and determine the effect of forest edges on the diversity of medicinal plants on the northern slopes and western slopes in the Gunung Tilu forest area. Line transect method was used to collect medicinal plant data. Sampling was done by making plots to analyze the composition, dominant species, diversity index, evenness index, and community similarity index. Furthermore, environmental variables such as temperature, humidity, sunlight intensity and soil pH were analyzed using the Spearman correlation test. The results showed that there were 89 species of medicinal plants classified into 41 families. The families with the largest number of medicinal plants came from the Asteraceae and Moraceae families. On the western slope, the understory, seedling, pole, and tree levels did not experience significant composition at various distance, but at the sapling level, changes occurred at a distance of 260 meters. On the northern slope, there were different variations in edge depth at each growth level where in understory, seedlings, and saplings, the edge depth reached up to 260 meters, while at the pole level, changes occurred at a distance of 240 meters and trees at 120 meters. This shows that tree communities adapt more quickly to environmental condition in the forest compared to other stages.